Investigation of Salix alba and Populus tremula leaf litter decomposition in the area of Lake Balaton and Kis-Balaton Wetland - Simon, Brigitta; Kucserka, Tamás; Anda, Angéla (Acta Agraria Debreceniensis, 2018)
Plant litter decomposition in inland waters contributes significantly to nutrient load, particularly in still waters, such as shallow lakes and wetlands. The decomposition rates of Salix alba and Populus tremula leaf litter was examined in Lake Balaton and Kis-Balaton Wetland, using litter bag technique. Leaf litter was incubated in small (ᴓ=3 mm) and large (ᴓ=900 μm) mesh size bags for the assessment of the relative contribution of macroinvertebrates to leaf litter decomposition. Dry mass, exponential decay coefficient and chemical parameters of water (pH, conductivity, NH4 +, NO3 -, SO4 2-, PO4 3-, Cl-) were determined. Leaf mass loss showed negative exponential pattern during the 168 days of the decomposition period. Leaf litter mass loss generally did not differ between the small and large mesh sizes, suggesting that macroinvertebrates generally have a negligible role in leaf decomposition in the winter period.